2011
DOI: 10.18806/tesl.v29i1.1088
|View full text |Cite
|
Sign up to set email alerts
|

ESL Teacher-Candidates’ Beliefs About Language

Abstract: How do ESL teacher-candidates grapple with beliefs about language during their professional training? In this article, we present the findings of a qualitative research study conducted in a large eastern Canadian university Bachelor of Education program. As Johnson (2010) has recently noted, despite extensive research and theoretical work that stresses the importance of functional conceptualizations of language based on social practice, much ESL teacher training still revolves around the skills needed to trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 35 publications
4
11
0
Order By: Relevance
“…Another participant in the present study accounted for her traditional teaching practice by time and curriculum requirements, since she emphasized that: "I had to obey the school's curriculum and time was limited to do more interactive activities" (Participant 1). This replicated Fleming, Bangou and Fellus' (2011) proposition that preservice teachers were restricted in integrating the content of teacher education into the practicum. Moreover, Barnard and Scampton's (2008) presumption that time could be an obstacle for teachers to employ more contextualized, communicative approaches might help to account for the inconsistency observed between the participants' reported beliefs and actual practices in the cooperating school.…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…Another participant in the present study accounted for her traditional teaching practice by time and curriculum requirements, since she emphasized that: "I had to obey the school's curriculum and time was limited to do more interactive activities" (Participant 1). This replicated Fleming, Bangou and Fellus' (2011) proposition that preservice teachers were restricted in integrating the content of teacher education into the practicum. Moreover, Barnard and Scampton's (2008) presumption that time could be an obstacle for teachers to employ more contextualized, communicative approaches might help to account for the inconsistency observed between the participants' reported beliefs and actual practices in the cooperating school.…”
Section: Discussionsupporting
confidence: 55%
“…Based on Borg's (1999) classification of teachers' cognitions about grammar instruction, these factors can broadly be categorized as "schooling", "teacher education" and "classroom experience" (p. 26). To begin with schooling, several studies (Busch, 2010;Farrell & Lim, 2005;Fleming, Bangou & Fellus, 2011) report that teachers' beliefs are influenced by their background as language learners. Farrell (1999) indicated that beliefs of all pre-service teachers participating in his study were shaped by their prior experiences as learners.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Many teachers 2 B. Gilliland hold deficit views of their multilingual students, seeing their poor performances on standardized tests as evidence of limited intellectual capacity (Rolstad 2014). Teacher education policy generally ignores L2 development (Bunch 2013;Fleming, Bangou, and Fellus 2011;Paterson 2010) or presents a reductive interpretation of Krashen's work, emphasizing input (reading) and output (writing) but not language (Gebhard and Harman 2011). Few states require mainstream teachers to take courses on working with multilingual learners, and none require coursework in linguistics (Stevens 2008;Samson and Collins 2012).…”
Section: Introductionmentioning
confidence: 99%
“…In the field of second language teacher education (SLTE), the publication of Freeman and Johnson's widely cited article, "Reconceptualizing the Knowledge-Base of Language Teacher Education" (1998), is considered one such moment. This cornerstone article is believed to have had a powerful impact on SLTE theory, research, and practice among members of the SLTE community (Faez, 2011;Fleming, Bangou, & Fellus, 2012;Salas, 2007), and those scholars and researchers directly involved in theorizing and researching issues related to SLTE. Freeman and Johnson (F&J) proposed a different view of what constitutes the knowledge base of SLTE, departing from a historical view of a "binary distinction between subject matter and learners" that resulted in a transmission perspective of language education (p. 406).…”
Section: Nous Examinons Les Citations De Fandj Y Compris La Façon Domentioning
confidence: 99%